Relationship Between the Onset of Ménière's Disease and Sympathetic Hyperactivity - Ishii, Masanori; Ishiyama, Gail; Ishiyama, Akira; Kato, Yujin; Mochizuki, Fumihiro; Ito, Yusuke (Frontiers in Neurology, 2022)
Objective: The pathogenesis of Ménière’s disease is still largely unknown; however, it is known to be strongly associated with stress. Excessive stress can cause hyperactivity of the sympathetic autonomic nervous system. With the aim of understanding changes in sympathetic hyperactivity before and after Ménière’s disease, we compared autonomic nervous function in patients in a stable phase of Ménière’s disease and that in healthy adults. We also gathered data over about 10 years on autonomic nervous function immediately before a Ménière’s attack. Study Design: Prospective study. Patients: Autonomic nervous function was analyzed in 129 patients in a stable phase of Ménière’s disease 31 healthy adult volunteers. In 9 patients, autonomic nervous function was also measured immediately before and after treatment of a vertigo attack. Main Outcome Measure: Power spectrum analysis of heart rate variability (HRV) of EEG/ECG and an infrared electronic pupillometer were used. Sympathetic and parasympathetic nervous function was measured. Results: There were no statistically significant differences in autonomic nervous function determined by HRV and electronic pupillometry between patients in a stable phase of Ménière’s disease and healthy adults. Sympathetic function as measured by electronic pupillometry parameters VD and T5 showed no difference between the affected and unaffected sides in the baseline data measured in the stable phase (VD: affected side is 31.02 ± 6.16 mm/sec, unaffected side is 29.25 ± 5.73 mm/sec; T5: affected side is 3.37 ± 0.43 msec, unaffected side is 3.25 ± 0.39 msec). In contrast, all 9 patients whose HRV data had been obtained just before an attack showed marked suppression of the parasympathetic nervous system and activation of the sympathetic nervous system. Electronic pupillometry also revealed an overactivation of the sympathetic nervous system on the affected side, just before the attacks. Analysis of sequential changes after the onset of an attack revealed that overactivation on the affected side was reduced after treatment, and no difference between affected and unaffected sides was observed 3 days after treatment. Conclusion: Detailed analysis of autonomic nervous function showed that immediately before an attack of Ménière’s disease, the sympathetic nervous system on the affected side was strongly overactivated.